2023
DOI: 10.3390/jpm13050739
|View full text |Cite
|
Sign up to set email alerts
|

Is Psychological Distress Associated with Self-Perceived Health, Perceived Social Support and Physical Activity Level in Spanish Adults with Diabetes?

Abstract: Depressive and anxiety symptoms are common in people with type 1 and type 2 diabetes mellitus. Physical activity and social support may prevent or reduce psychological distress in this population. This study aimed to analyse the associations between psychological distress, self-perceived health (SPH), perceived social support (PSS) and physical activity level (PAL) in adults with a diabetes mellitus diagnosis from Spain. A cross-sectional study based on data from the Spanish National Health Survey (ENSE2017) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…This finding was consistent with our hypothesis 3 and previous studies. 46 47 A cross-sectional study 48 enrolled 133 hypertensive stroke patients 6 months after discharge in China have shown the perceptions of chronic illness resources received from healthcare teams, family and friends, and the community were positively correlated with health behaviour. Tan et al 49 conducted a cross-sectional study among 350 stroke participants in China and found that PSS had a direct positive effect on rehabilitation motivation.…”
Section: Discussionmentioning
confidence: 99%
“…This finding was consistent with our hypothesis 3 and previous studies. 46 47 A cross-sectional study 48 enrolled 133 hypertensive stroke patients 6 months after discharge in China have shown the perceptions of chronic illness resources received from healthcare teams, family and friends, and the community were positively correlated with health behaviour. Tan et al 49 conducted a cross-sectional study among 350 stroke participants in China and found that PSS had a direct positive effect on rehabilitation motivation.…”
Section: Discussionmentioning
confidence: 99%
“…Physical self-esteem is an important factor influencing young people’s well-being. This factor is particularly relevant during adolescence and intensive development, as this is the period when personality is formed and is closely linked to young people’s mental health and well-being [ 62 ]. Body image is an important part of the complex mechanism that is self-identity.…”
Section: Discussionmentioning
confidence: 99%